Interaction of cyclic thiadiynes with CpCo(COD): selectivity and reactivity - Gleiter, Rolf; Claßen, Jörg; Rausch, Bernhard J.; Oeser, Thomas; Rominger, Frank (Journal of organometallic chemistry, 2002)
The reaction of CpCo(COD) with several cyclic thiadiynes leads to selective product formation; according to their ring size either (2,5)[2.2]thiophenophanes or CpCo-stabilized cyclobutadienes were formed. The outcome of the reaction can be attributed to the geometry in the transition states, 6 and 11. X-ray structure analyses of the reacting thiacycles and the isolated CpCo compounds are given and correlated with the tautness of the cobaltols.